2023
DOI: 10.1038/s41598-023-42763-1
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a familial hypercholesterolemia model in non-human primate

Akira Sato,
Tomoyuki Tsukiyama,
Masahiro Komeno
et al.

Abstract: Familial hypercholesterolemia (FH) is an inherited autosomal dominant disorder that is associated with a high plasma level of low-density lipoprotein (LDL) cholesterol, leading to an increased risk of cardiovascular diseases. To develop basic and translational research on FH, we here generated an FH model in a non-human primate (cynomolgus monkeys) by deleting the LDL receptor (LDLR) gene using the genome editing technique. Six LDLR knockout (KO) monkeys were produced, all of which were confirmed to have mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…FH is an inherited autosomal dominant disorder with a raised LDL plasma level, so patients with FH have a high risk of xanthomas. 5 In this case, no obvious diseases affecting lipid metabolism such as liver and kidney diseases and diabetes were found by routine examination, and blood lipid tests showed significant increases in serum cholesterol, especially LDL level. In addition, the patient reported that her grandfather and father also had hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 69%
“…FH is an inherited autosomal dominant disorder with a raised LDL plasma level, so patients with FH have a high risk of xanthomas. 5 In this case, no obvious diseases affecting lipid metabolism such as liver and kidney diseases and diabetes were found by routine examination, and blood lipid tests showed significant increases in serum cholesterol, especially LDL level. In addition, the patient reported that her grandfather and father also had hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 69%